2005
DOI: 10.1002/chin.200552187
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Nucleic Acid Analogues Consisting of a Benzene—Phosphate Backbone.

Abstract: Nucleic acids U 0700 Synthesis and Properties of Nucleic Acid Analogues Consisting of a Benzene-Phosphate Backbone. -(UENO, Y.; KATO, T.; SATO, K.; ITO, Y.; YOSHIDA, M.; INOUE, T.; SHIBATA, A.; EBIHARA, M.; KITADE*, Y.; J. Org. Chem. 70 (2005) 20, 7925-7935; Dep. Biomol. Sci., Fac. Eng., Gifu Univ., Yanagido, Gifu 501-11, Japan; Eng.) -Lindner 52-187

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…[17][18][19] Therefore, we consider that BP at the 3 0 -overhang region may be associated with the PAZ domain of Ago2. 13,14 These findings were reflected by the evidence that the protein level of ERK5, one of the major targets of miR-143, was downregulated in accordance with the activities of the various synthetic miR-143s with modified passenger sequences. Furthermore, the isolation of miRNA by using anti-Ago2 antibody indicated a higher level of miR-143BP/3 0 -2 M in Ago2-binding miRNAs than that of miR-143BP/4 M, which probably caused the more potent suppression of ERK5 expression.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[17][18][19] Therefore, we consider that BP at the 3 0 -overhang region may be associated with the PAZ domain of Ago2. 13,14 These findings were reflected by the evidence that the protein level of ERK5, one of the major targets of miR-143, was downregulated in accordance with the activities of the various synthetic miR-143s with modified passenger sequences. Furthermore, the isolation of miRNA by using anti-Ago2 antibody indicated a higher level of miR-143BP/3 0 -2 M in Ago2-binding miRNAs than that of miR-143BP/4 M, which probably caused the more potent suppression of ERK5 expression.…”
Section: Discussionmentioning
confidence: 88%
“…13,14 Deprotection of bases and phosphates was performed in concentrated NH 4 OH/EtOH (3:1, v/v) at room temperature for 12 h. The 2 0 -tert-butyldimethylsilyl groups were removed by treatment for 12 h with 1.0 M tetrabutylammonium fluoride in tetrahydrofuran at room temperature.…”
Section: Modification For Higher Nuclease-resistance Property Of Mirnmentioning
confidence: 99%
“…Our recent work has revealed that changing the structure of the passenger strand of the miR-143 duplex enhanced the growth inhibition of human colon cancer DLD-1 cells and that chemical modification of the 3′-overhang of miR-143 using aromatic moieties, such as benzene(B)-pyridine(P) analogs (BP-type), improved its resistance against nucleases (13,14). The administration of such chemically modified miR-143BPs via intravenous injection resulted in a potent tumor-suppressive effect on xenografted human colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, authors reported the synthesis and properties of oligonucleotide analogs containing benzene‐phosphate backbone which is highly resistant to nuclease activity (Ueno et al., , ). However, the oligonucleotides were unable to form stable duplexes with complementary RNA and DNA.…”
Section: Commentarymentioning
confidence: 99%